Neuroprotective effect of naringenin against MPTP-induced oxidative stress. (3rd June 2019) - Sugumar, Mani; Sevanan, Murugan; Sekar, Sathiya
Abstract: Background: Parkinson's disease is the most common neurodegenerative disorder, characterized by loss of dopaminergic neurons in substantia nigra and depletion of dopamine in striatum due to excitotoxicity, oxidative stress and many other factors may contribute to MPTP- and PD-related neurodegeneration. The present study deals with the neuroprotective effect of Naringenin (NGN), a bioflavonoid against MPTP-induced Parkinson's disease in the mouse model. Methods: Healthy male C57BL/6J mice (18–22 g b wt) were pretreated with NGN [25, 50, 100 mg/kg/b.wt, p.o] once daily for 5 days. Thereafter, 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) (80 mg/kg b.wt, i.p) was given in two divided doses (2 × 40 mg/kg at 16 h interval). The animals were observed for motor functions 48 h after the first MPTP injection. After completion of behaviour tasks, all animals were euthanized to dissect out the brain and used for biochemical, molecular and histopathological investigations. Results: Pretreatment of NGN significantly reversed the toxic effects of MPTP by reducing LPO levels and increasing the activities of glutathione reductase and catalase along with improved behavioural performance. Interestingly, pre-treatment with NGN down-regulated iNOS expression level in MPTP intoxicated mice brain. In addition, the histopathological evaluation revealed that NGN decreased the nuclear pigmentation and cytoplasmic vacuolation in the substantia nigra and striatal regions when compared to MPTP-intoxicated mice brain. Discussion: The present study showed that NGN exerts neuroprotection by suppressing oxidative stress via antioxidant mechanisms. The above finding suggests that NGN may act as a potential target in the management of PD.